Genetic heterogeneity in cystinuria: the SLC3A1 gene is linked to type I but not to type III cystinuria. - Calonge, M J (1995)
Cystinuria is an autosomal recessive amino-aciduria where three urinary phenotypes have been described (I, II, and III). An amino acid transporter gene, SLC3A1 (formerly rBAT), was found to be responsible for this disorder. To assess whether mutations in SLC3A1 are involved in different cystinuria phenotypes, linkage with this gene and its nearest marker (D2S119) was analyzed in 22 families with type I and/or type III cystinuria. Linkage with heterogeneity was proved (alpha = 0.45; P < 0.008). Type I/I families showed homogeneous linkage to SLC3A1 (Zmax > 3.0 at theta = 0.00; alpha = 1), whereas types I/III and III/III were not linked. Our data suggest that type I cystinuria is due to mutations in the SLC3A1 gene, whereas another locus is responsible for type III. This result establishes genetic heterogeneity for cystinuria, classically considered as a multiallelic monogenic disease.